Microbial Tuning of the Mammalian Immune System. Issue 5 (May 2017) - Pamer, Eric G.
Abstract : Bacterial species constituting the intestinal microbiota are implicated in maintenance of health but also pathogenesis of inflammatory disease. The compositional complexity of the microbiota and metabolic interdependencies of microbial species challenge our ability to attribute host responses to specific bacterial strains. Studies using gnotobiotic mice, however, are providing important insights.